Predictors of recurrent stroke after embolic stroke of undetermined source in the RE‐SPECT ESUS trial: brief communication - Del Brutto, Victor J.; Diener, Han‐Christoph; Easton, J. Donald; Granger, Christopher B.; Cronin, Lisa; Kleine, Eva; Grauer, Claudia; Brückmann, Martina; Toyoda, Kazunori; Schellinger, Peter D.; Lyrer, Philippe; Molina, Carlos A.; et al. (Journal of the American Heart Association, 2022)
Background We sought to determine recurrent stroke predictors among patients with embolic strokes of undetermined source (ESUS). Methods and Results We applied Cox proportional hazards models to identify clinical features associated with recurrent stroke among participants enrolled in RE‐SPECT ESUS (Randomized, Double‐Blind, Evaluation in Secondary Stroke Prevention Comparing the Efficacy and Safety of the Oral Thrombin Inhibitor Dabigatran Etexilate Versus Acetylsalicylic Acid in Patients With Embolic Stroke of Undetermined Source) trial, an international clinical trial evaluating dabigatran versus aspirin for patients with ESUS. During a median follow‐up of 19 months, 384 of 5390 participants had recurrent stroke (annual rate, 4.5%). Multivariable models revealed that stroke or transient ischemic attack before the index event (hazard ratio [HR], 2.27 [95% CI, 1.83-2.82]), creatinine clearance <50 mL/min (HR, 1.69 [95% CI, 1.23-2.32]), male sex (HR, 1.60 [95% CI, 1.27-2.02]), and CHA2DS2‐VASc ≥4 (HR, 1.55 [95% CI, 1.15-2.08] and HR, 1.66 [95% CI, 1.21-2.26] for scores of 4 and ≥5, respectively) versus CHA2DS2‐VASc of 2 to 3, were independent predictors for recurrent stroke. Conclusions In RE‐SPECT ESUS trial, expected risk factors previously linked to other common stroke causes were associated with stroke recurrence. These data help define high‐risk groups for subsequent stroke that may be useful for clinicians and for researchers designing trials among patients with ESUS. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT02239120.
Ursprünglich veröffentlicht: 3 Jun 2022
Gesehen am 09.01.2024